Influence of Aging Time on Compressive Strength of Silica Fume Reinforced High Strength Concrete Composite (المجلة الدولية للبحوث العلمية, 2024)
The goal of this study is to gather a High Strength Concrete (HSC) composite reinforced by silica fume and superplasticizers. Specimens are Cured by water and tested after aging time of 3, 7, 28 days. Specimens are cubes of 150 and 200 mm and 150x300mm cylinder. The aim is to get mean strength of 80- 85 MPa, and determination of physical properties of the materials used, which are basic components of the High Strength Concrete (HSC) composites. After designing mix proportions, according to design requirements some adjustments were done. Both fresh and hardened properties of the specimens were tested under standard condition (curing schemes, setting time, comp.str. etc). Compressive strength test results were gathered and compared with the requirements.